2016
DOI: 10.1111/edt.12260
|View full text |Cite
|
Sign up to set email alerts
|

Association between eruption state of the third molar and the occurrence of mandibular angle fractures

Abstract: Fractures of the mandibular angle are more likely to appear in patients with retained third molars which might be due to the reduced bone mass. Once the wisdom teeth have erupted, the bone structure is more solid and more resistant to external forces and the development of fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…2,3 Etiologic factors of mandibular fractures include motor vehicle accidents, assaults, falls, and sport activities including cycling. [4][5][6] Most mandibular fractures are reported in male patients. According to the literature, the average age of patients with an angle fracture (24.5 to 37.95 years) is not different from that of patients with a condylar fracture (26.35 to 36.9 years).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Etiologic factors of mandibular fractures include motor vehicle accidents, assaults, falls, and sport activities including cycling. [4][5][6] Most mandibular fractures are reported in male patients. According to the literature, the average age of patients with an angle fracture (24.5 to 37.95 years) is not different from that of patients with a condylar fracture (26.35 to 36.9 years).…”
mentioning
confidence: 99%
“…6,8 In addition, the treatment of condylar fractures is more challenging and associated with higher morbidity than the management of an angle fracture. 5,[19][20][21] Thus, the indications for the prophylactic removal of an impacted lower third molar are inconsistent [22][23][24] ; furthermore, geographic locations can affect the etiologic factors of mandible fractures. Notably, systematic reviews on this topic have reported inconsistent results, and this discrepancy indicates the need for additional studies with large sample sizes.…”
mentioning
confidence: 99%
“…Adicionalmente, as inserções musculares locais e a oclusão criam uma área de tensão na borda superior do ângulo mandibular e uma área de compressão na borda inferior, de forma que a presença de terceiros molares que interferem na continuidade das estruturas de reforço ósseo pode criar zonas de maior fragilidade. Consequentemente, forças externas propagadas na região de ângulo precisam de menos intensidade para que fraturas ocorram (SAMIERAD et al, 2018;RAHIMI-NEDJAT et al, 2016;SOÓS et al, 2020). Assim, dado o impacto causado pela presença dos terceiros molares nessa região, estudos sugerem que há variação de interferência de acordo com diversos fatores como direção e impacto da força aplicada, padrão de carga oclusal, bem como o posicionamento desses dentes (GIOVACCHINNI et al, 2018;MEHRA et al, 2019) Contudo, tais manuscritos não discorrem sobre os fatores envolvidos nessa relação, por isso, constatamos a necessidade de mais estudos que discorram sobre a influência da angulação dos dentes inclusos nos casos de fraturas angulares.…”
Section: Brazilian Journal Ofunclassified
“…Nevertheless, anatomical reasons determine some weak points where the bone mass is more sparse, and fractures occur more often at the condyle or mandibular angle when third molars are present . Furthermore, the incidence of concomitant fractures varies widely and is the subject of ongoing discussion in the literature .…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Nevertheless, anatomical reasons determine some weak points where the bone mass is more sparse, and fractures occur more often at the condyle or mandibular angle when third molars are present. 11 Furthermore, the incidence of concomitant fractures varies widely and is the subject of ongoing discussion in the literature. 12 Analyzing specific patterns and mechanisms of fracture can be helpful to increase the sensitivity for detection of injuries during the clinical examination and when imaging such as cone beam computerized tomography (CBCT).…”
mentioning
confidence: 99%